Towards a Non-Intrusive Pulse Oximetry System with Long-Term Mobile Monitoring - Arabi, Mohammad N. (My University, 2010)
The percentage of arterial oxygen in the blood is a vital physiological sign used by clinicians and doctors to monitor the health of patients under critical conditions in the hospital; the technology used universally to monitor this is known as pulse oximetry. The sensors most commonly used in the hospitals are of reflection type such that the LEDs and the photodetector (PD) are placed on opposite ends of short distance body tissue, e.g. finger. There has been an increased demand for monitoring patients who have suffered a stroke and are recovering in their homes, and simply the elderly. For such persons, staying in the hospital is unnecessary and undesirable psychologically. As such, a system is to be designed such that patients can monitor their physiological signals, and only contact the doctor when it is imperative to do so. With the comfort of the patient in mind, the system must be unobtrusive in nature such that it does not impede any of their simply daily activities. The sensor used in the system is of reflectance type, i.e. LEDs and PD placed on the same side, and is to be placed on the pectoral region. The pectoral region is chosen for the ease of measuring electrocardiogram (ECG) signals, another vital physiological signal. Due to lesser blood perfusion in that anatomical region, the question remains as to whether signals could be acquired faithfully there. Results have shown that although signals can be obtained, they vary greatly mainly due to motion artifacts. The system could be improved if complex digital signal processing algorithms are used.
Keywords: Pulse Oximetry; Reflectance Sensor; Motion Artifacts; Wireless; Automatic Gain Control; Biomedical; Electrical and Computer Engineering; Biomedical